Proton radiation effects on the self-aligned triple gate SOI p-type Tunnel FET output characteristic - Torres, H. L. F.; Martino, J. A.; Rooyackers, R.; Vandooren, A.; Simoen, E.; Claeys, C.; Agopian, P. G. D. [UNESP]; IEEE (Ieee, 2017)
This paper reports for the first time the study of radiation effects on triple gate SOI tunnel FETs. In this work, devices with 1 mu m width and three different channel lengths were exposed to a 600 keV proton radiation source and their current-voltage behavior was analyzed after 1 Mrad(Si) of accumulated total dose, comparing the results obtained before and after irradiation. It was possible to notice a drain current decrease in the shorter channel devices. However, this total dose influence was not so prominent in the longer channel ones. The reasons for both phenomena is discussed based on the competition between the drain current split and the high channel resistance.
Keywords: Proton radiation; TFET; SOI; Characterization